Vaginal Angiomyofibroblastoma: A Case Report and Review of Diagnostic Imaging - Sarah Eckhardt; Renee Rolston; Suzanne Palmer; Begum Ozel (Case Reports in Obstetrics and Gynecology)
Background. Angiomyofibroblastoma (AMFB) is a benign mesenchymal tumor most commonly found in the female genital tract of premenopausal women. Although rare, AMFB is an important consideration in the differential diagnosis of vulvar and vaginal masses, as it must be distinguished from aggressive angiomyxoma (AA), a locally recurrent, invasive, and damaging tumor with similar clinical and pathologic findings. Case. We describe a patient with a 4 cm vaginal AMFB and the relevant preoperative radiographic imaging findings. Conclusion. Preoperative diagnosis of AMFB remains difficult. Common findings on magnetic resonance imaging and transvaginal sonography are described. We conclude that both transvaginal ultrasound and MRI are potentially useful imaging modalities in the preoperative assessment of vulvar and vaginal AMFB, with more data needed to determine superiority of one modality over the other.